Sistem Desalinasi Membran Reverse Osmosis (RO) untuk Penyediaan Air Bersih - Linda A Yoshi; I Nyoman Widiasa (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Development of tourism has an impact on the water demand. The amount of clean water is not comparable ofrequirement. Theother alternatifis needed to get clean water of water sources and technologies. One of technology that can be used is desalination and water source can be used sea water and brackish water. Desalination technology is divided into two: thermal processes and membrane processes. Currently, reverse osmosis membrane separation is more favorable than thermal process. Desalination costs are more affected by plant capacity  and energy consumption. The greater plant will be cheaper than smaller palnt. In addition to these two factors, desalination cost is affected by the place where the RO desalination plant is installed. The cost of desalination at each country will bedifferent even thoughthe costof desalinationin Indonesia has not been recorded properly.